Rancangan Manajemen Jaringan dengan Integrasi Otomatisasi Menggunakan Internet of Things - Firmansyah, Aditya Pandu; Ramadhan, Muhammad Fadlan; Wahyudi, Wahyudi (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The Internet of Things (IoT) is one of the newest technologies that schools have not yet fully embraced. As a result, there has been wasteful use of energy and inadequate usage of classrooms. The goal of this research is to create and evaluate an IoT system in schools that uses RFID Card and Reader to improve classroom usage and energy efficiency. There are three research methods used which involve running system analysis, proposed system, and prototyping methods. Through reviews of the literature, data was gathered. After then, the data was examined to find issues and system requirements. Additionally, an Internet of Things system design was developed and put to the test via simulation with Cisco Packet Tracer. The Internet of Things automation design was in line with the scenario that the researchers had planned, according to the outcomes of the experiments and simulations. It is established that the system increases classroom productivity while conserving energy. It is anticipated that this system's implementation will assist schools in raising the standard of instruction and fostering a more favorable learning environment.